Applying the Risk–Need–Responsivity (RNR) Model to Transgender Women in the Criminal Justice System - Yerke, Adam F. (The prison journal, 2025)
Transgender women are at least twice as likely as cisgender people to be incarcerated in their lifetimes, and, in custody, they experience harassment, abuse, and denial of affirming healthcare. Despite several legal and policy changes intended to improve these conditions, there has been little discussion about the need for evidence-based rehabilitation with the population. This article examines the use of the risk–need–responsivity (RNR) model with transgender women in the criminal justice system and discusses how it can be beneficial for tailoring rehabilitation services to address the unique needs of the population, thereby improving opportunities for successful community reintegration.